Study of Cerium and Lanthanum Conversion Coatings on AZ63 Magnesium Alloy Surface. Issue 2 (February 2015) - Lin, Chen; Changguo, Chen; Ningning, Wang; Jimin, Wang; Ling, Deng
Abstract The influence of cerium and lanthanum conversion coatings on AZ63 magnesium alloy surface was investigated by Tafel polarization curves, electrochemical impedance spectroscopy (EIS), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX) and X-ray photoelectron spectroscopy (XPS). The results show that the dual rare-earth conversion film treated in the mixture solution containing cerium nitrate and lanthanum nitrate is denser and more uniform than that in single rare-earth solution. EDX and XPS analysis demonstrates that the coatings are composed of rare earth oxides and hydrated hydroxides. The cerium and lanthanum conversion coatings can improve the corrosion resistance of AZ63 magnesium alloy evidently. The inhibition effect of dual rare-earth film on magnesium alloy increases with the increase of immersion time. With the extension of aging time, the inhibition effect increases first and then decreases. The coating aged for 48 h possesses the best inhibition effect.